The benefit of adding a physiotherapy or occupational therapy intervention programme to a standardized group-based interdisciplinary rehabilitation programme for patients with chronic widespread pain: a randomized active-controlled non-blinded trial. (August 2019) - Amris, Kirstine; Bülow, Cecilie von; Christensen, Robin; Bandak, Elisabeth; Rasmussen, Marianne Uggen; Danneskiold-Samsøe, Bente; Wæhrens, Eva E
Objective: To evaluate the benefit of adding occupational therapy or physiotherapy interventions to a standard rehabilitation programme targeted for chronic widespread pain. Design: Randomized active-controlled non-blinded trial. Subjects: Women with chronic widespread pain recruited in a tertiary outpatient clinic. Methods: Participants were randomized to a two-week, group-based standard rehabilitation programme followed by 16 weeks of group-based occupational therapy (Group BOT, n  = 43) or 16 weeks of group-based physiotherapy (Group BPT, n  = 42). Group A only received the two-week rehabilitation programme acting as comparator ( n  = 96). Outcomes: Primary outcomes were the Assessment of Motor and Process Skills and Short Form-36 (SF36) Mental Component Summary score. Results: Mean changes in motor and process ability measures were clinically and statistically insignificant and without differences across the three groups assessed 88 weeks from baseline. Motor ability measures: −0.006 (95% confidence interval (CI): −0.244 to 0.233) in Group BOT ; −0.045 (95% CI: −0.291 to 0.202) in Group BPT ; and −0.017 (95% CI: −0.248 to 0.213) in Group A, P  = 0.903. Process ability measures: 0.087 (95% CI: −0.056 to 0.231) in Group BOT ; 0.075 (95% CI: −0.075 to 0.226) in Group BPT ; and 0.072 (95% CI: −0.067 to 0.211) in Group A, P  = 0.924. Mean changes in patient-reported outcomes were likewise small; clinically and statistically insignificant; and independent of group allocation, except for the SF36 mental component summary score in the BPT group: 8.58 (95% CI: 1.75 to 15.41). Conclusion: Participants were on average stable in observation-based measures of functional ability and patient-reported outcomes, except in overall mental well-being, favouring the enhanced intervention. Efficacy of additional interventions on functional ability remains uncertain.